Effects of Therapeutic Hypothermia on Normal and Ischemic Heart - Yamada, Kelly P.; Kariya, Taro; Aikawa, Tadao; Ishikawa, Kiyotake (Frontiers in Cardiovascular Medicine, 2021)
Therapeutic hypothermia has been used for treating brain injury after out-of-hospital cardiac arrest. Its potential benefit on minimizing myocardial ischemic injury has been explored, but clinical evidence has yet to confirm positive results in preclinical studies. Importantly, therapeutic hypothermia for myocardial infarction is unique in that it can be initiated prior to reperfusion, in contrast to its application for brain injury in resuscitated cardiac arrest patients. Recent advance in cooling technology allows more rapid cooling of the heart than ever and new clinical trials are designed to examine the efficacy of rapid therapeutic hypothermia for myocardial infarction. In this review, we summarize current knowledge regarding the effect of hypothermia on normal and ischemic hearts and discuss issues to be solved in order to realize its clinical application for treating acute myocardial infarction.